An Atlas of Transcription Factors Expressed in Male Pupal Terminalia of Drosophila melanogaster. Issue 12 (1st December 2019) - Vincent, Ben J; Rice, Gavin R; Wong, Gabriella M; Glassford, William J; Downs, Kayla I; Shastay, Jessica L; Charles-Obi, Kenechukwu; Natarajan, Malini; Gogol, Madelaine; Zeitlinger, Julia; Rebeiz, Mark
Abstract: During development, transcription factors and signaling molecules govern gene regulatory networks to direct the formation of unique morphologies. As changes in gene regulatory networks are often implicated in morphological evolution, mapping transcription factor landscapes is important, especially in tissues that undergo rapid evolutionary change. The terminalia (genital and anal structures) of Drosophila melanogaster and its close relatives exhibit dramatic changes in morphology between species. While previous studies have identified network components important for patterning the larval genital disc, the networks governing adult structures during pupal development have remained uncharted. Here, we performed RNA-seq in whole Drosophila melanogaster male terminalia followed by in situ hybridization for 100 highly expressed transcription factors during pupal development. We find that the male terminalia are highly patterned during pupal stages and that specific transcription factors mark separate structures and substructures. Our results are housed online in a searchable database (https://flyterminalia.pitt.edu/ ) as a resource for the community. This work lays a foundation for future investigations into the gene regulatory networks governing the development and evolution of Drosophila terminalia.